2006
DOI: 10.1186/bf03352594
|View full text |Cite
|
Sign up to set email alerts
|

Crustal structure of the ocean-island arc transition at the mid Izu-Ogasawara (Bonin) arc margin

Abstract: Wide-angle refraction experiments were conducted to reveal the crustal structure at the transition between the intra-oceanic island arc crust of the mid Izu-Ogasawara (Bonin) arc and the backarc oceanic crust of the Shikoku Basin. The island arc crust consists of an upper crust about 5 km thick with a P-wave velocity <6.0 km/s, a middle crust 5 km thick with a P-wave velocity of 6.0-6.3 km/s, and a lower crust 10 km thick with a P-wave velocity of 6.8-7.2 km/s. The total crustal thickness is about 20 km. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 7 publications
(9 reference statements)
2
20
0
1
Order By: Relevance
“…In this study, we did not find any crustal thinning beneath the KE on SPr10 and SPr7. This result may be correlated with the smaller bathymetric offsets of the escarpment beneath SPr10 and SPr7 compared with that of Nishizawa et al (2006). Crusts with a V p < 3.5 km/s thicken eastward from around the KE, and this thickening is related to the volcanic activity of the IOA.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In this study, we did not find any crustal thinning beneath the KE on SPr10 and SPr7. This result may be correlated with the smaller bathymetric offsets of the escarpment beneath SPr10 and SPr7 compared with that of Nishizawa et al (2006). Crusts with a V p < 3.5 km/s thicken eastward from around the KE, and this thickening is related to the volcanic activity of the IOA.…”
Section: Discussionmentioning
confidence: 83%
“…In the SB, P n velocity estimated in this study for the spreading direction is at most 8.1 km/s. On the other hand, P n velocity for the northsouth line of Nishizawa et al (2006) to the south of SPr10 (Fig. 1) was ∼8 km/s.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The V p model of ECr31, along the arc line, reveals a typical island structure, the same as the Japan arc compiled by Iwasaki and Sato (2009). A high V p of around 7.2 km/s at the bottom of the lower crust beneath intra-oceanic island arcs, such as the Izu-Ogasawara island arc and the Kyushu-Palau Ridge (e.g., Nishizawa et al 2006Nishizawa et al , 2016, was not found in the Ryukyu arc. None of the arc crusts of the Japan Islands have such a high V p at the bottom of the lower crust, which might indicate differences in the evolution tectonics between the intra-oceanic island arcs and the Japan island arcs.…”
Section: Ryukyu Island Arcmentioning
confidence: 93%
“…Black arrow indicates relative plate motion between the Philippine Sea plate and Eurasian plate (Seno et al 1993). The GMT software (Wessel and Smith 1998) was used to draw the maps arc-like crust (several kilometers thicker than typical oceanic crust) exists just south of the ISTL (Nakanishi et al 1998;Nishizawa et al 2006;Kodaira et al 2008), leaving the open question of the nature of the Philippine Sea plate subducting beneath the ISTL.…”
Section: Introductionmentioning
confidence: 99%